The Development of Innovation and Chemical Entrepreneurship Module for Pre-University Students: An Analysis Phase of ADDIE Model - Ramly, Siti Nor Fazila; Ahmad, Nur Jahan; Mohd Said, Hardimah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The present study is the initial stage; an analysis phase, which aimed to identify suitability and the need of the module development for pre-university students. The module will be developed based on two main elements: Innovation and Chemical Entrepreneurship (CEP). Using ADDIE instructional model, through analysis phase, the suitability, and the need for the module development, are identified through three collected data: (a) module of suitability in semi-structured interview, (b) student need analysis questionnaire, and (c) module of need analysis questionnaire. Five experts in STEM, Chemistry, innovation, and entrepreneurship area are interviewed to collect data (a) and will give the suitability and arrangement of the module content. Whereas the data survey (b) is collected from 60 pre-university students through random sampling from a college in Penang, Malaysia, and data survey for (c) is collected from all 40 Chemistry Lecturers. The qualitative interview is necessary to confirm the suitability of the main elements; innovation and Chemical Entrepreneurship in the module, while the quantitative data from two surveys; (b) and (c) give confirmation on components and requirements for the development of the modules from the students and the lecturers perspective. Data analysis for (a) was performed by using ATLAS.ti Version 22, whereas data analysis for (b) and (c) was performed through descriptive statistics. The qualitative data obtained from (a) confirmed the suitability of innovation and Chemical Entrepreneurship elements to be integrated into the learning module for pre-university, and the quantitative data from (b) and (c) successfully listed main components to be included in the module, such as learning outcomes, enhancement activities and reflections. The findings indicated that it is suitable and there is a need to develop i-CEP Module for pre-university studentsKeywords: analysis phase, innovation, chemical entrepreneurship, learning module, STEM approach.